2013
DOI: 10.1063/1.4817012
|View full text |Cite
|
Sign up to set email alerts
|

A-centers in silicon studied with hybrid density functional theory

Abstract: Density functional theory employing hybrid functional is used to gain fundamental insight into the interaction of vacancies with oxygen interstitials to form defects known as A-centers in silicon. We calculate the formation energy of the defect with respect to the Fermi energy for all possible charge states. It is found that the neutral and doubly negatively charged A-centers dominate. The findings are analyzed in terms of the density of states and discussed in view of previous experimental and theoretical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 32 publications
7
40
0
Order By: Relevance
“…GeVO transits from charge neutral to charge -2 at 0.47 eV, similar to previous findings for the VO defect, 22 where the formation energy of the charge neutral VO defect is 4.3…”
Section: Resultssupporting
confidence: 78%
“…GeVO transits from charge neutral to charge -2 at 0.47 eV, similar to previous findings for the VO defect, 22 where the formation energy of the charge neutral VO defect is 4.3…”
Section: Resultssupporting
confidence: 78%
“…This of course assumes that migration barriers will be similar and that competing structures will not readily form at higher temperatures. At any rate though it is demonstrated that the C i O i (Si I ) 2 cluster forms and that two configurations can acquire significant concentrations in good agreement with a recent experimental study [15].…”
Section: Resultssupporting
confidence: 68%
“…When considering high irradiation dose the C i O i may attract a Si I 's to form the C i O i (Si I ) complex (C 4 ) and thereafter even larger complexes such as the C i O i (Si I ) 2 [16,[20][21][22][23]. In a recent study Angeletos et al [15] introduced a model concerning a transformation of the C i O i (Si I ) complex to the formation of C i O i (Si I ) n (2 ≤ n ≤ 4) complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of the present computational approach has been discussed in a recent study on vacancies and the A-center in Si, 30,31 which we extend to the case of the Gcenter. Two stable structural configurations of C i C s (A-and B-type 16 ) are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%